The sound of gesture: For violin, sensors and computer - Wishart, Stevie (Stevie Wishart, 2010)
The Sound of Gesture, for violin, sensors and computer, is a series of compositions for violin, sensors and computer which are conceived as visual pieces & filmed by Berlin video artist Yvonne Mohr. The Sound of Gesture can be performed as a live concert event and/or an exhibition/gallery installation, which can also incorporate live performance.A hybrid of music technology, interactivity, real-time sound processing, music gesture and the violin, improvisation & electroacoustic composition.The Sound of Gesture was release as special cd/dvd in 2010.Instrumentation: violin, sensors & computer sound transformation/synthesis